Penerapan model pembelajaran problem based learning untuk meningkatkan gambaran keterampilan berhitung pada siswa kelas IV SD - Nikita Novianti; Asep Samsudin; Rina Rohmawati (COLLASE (Creative of Learning Students Elementary Education), 2023)
The application of numeracy skills is a skill that must be possessed by students with feedback. This study aims to determine the PBL learning model in the application of numeracy skills to elementary school students. This research is motivated by the problems that occur, namely the lack of numeracy skills in students of SDN 197 Karang Taruna Karangsari. Based on this, the researchers used the PBL (Problem Based Learning) model to overcome problems at SDN 197 Karang Taruna Karangsari. Numeracy skills from experts are very relevant to describe numeracy skills using the PBL (Problem Based Learning) model which has the characteristics of problem-based learning. The research method used is descriptive qualitative research. The research subjects were fourth grade students at SDN 197 Karang Taruna Karangsari totaling 40 students. Based on the results of the study, it showed that students' numeracy skills were very good, learning was also very enjoyable and students were more confident about learning through a problem-based learning model. It can be said that this PBL learning model is very relevant in knowing the description of numeracy skills in class IV students at SDN 197 Karang Taruna Karangsari.